Towards equitable and inclusive climate adaptation policies and practices in Vietnam’s Mekong Delta - Bernardo, Eisen (CGIAR System Organization, 2022)
The ‘Science Connections for Better Governance and Sustainable Development in the Mekong Delta’ policy dialogue was held in Can Tho City, Vietnam, on November 30, 2022. The event was designed to increase awareness and build the science-based decision-making capacity among provincial officials in the Mekong Delta, the CGIAR Initiative on Securing the Food Systems of Asian Mega-Deltas for Climate and Livelihood Resilience (AMD), and the Mekong Environment Forum.